IDENTIFICATION STUDENTSâ€™ DIFFICULTIES IN WRITING HORTATORY EXPOSITION AMONG HIGH INTERMEDIATE LEVEL - Paskal, Emanuel; Sada, Clarry; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aims to identify studentsâ€™ difficulties in writing hortatory exposition text at high intermediate level in Gajahmada English course. The method used is a descriptive study. The sample of the study is 10 students at high intermediate level of Gajahmada English course. The tool of data collecting was a written test that the students wrote hortatory exposition text. The finding showed the average of studentsâ€™ score is â€œ60.2â€ which is categorize â€œDifficultâ€. In grammar, students difficulties in arranging the tense and the compound-complex sentences. In mechanic, students difficulties in spelling, punctuation and word choice. In vocabulary, students difficulties in using of personal noun, abstract noun, general noun, action verb, verb, adverb and adjectives. In content, students able wrote the text, but their difficulties on the relevant details among thesis, arguments and recommendation. Keywords: Identification, studentsâ€™ difficulties, hortatory exposition Abstrak : Penelitian ini bertujuan mengidentifikasi kesulitan siswa menulis teks hortatory exposition pada level high intermediate di bimbingan belajar Gajahmada. Metode penelitian ini adalah penelitian deskriptif. Peserta penelitian adalah siswa bimbingan belajar Gajahmada level high intermediate, terdapat 10 peserta sebagai sampel. Alat mengumpulkan data yaitu sebuah tes tertulis, yakni siswa menulis teks hortatori exposisi. Hasil penelitian menunjukkan rata-rata nilai 60,2 dikategorikan â€œsulitâ€. Struktur bahasa, siswa kesulitan menyusun struktur kalimat dan penggunaan kalimat majemuk setara â€“ bertingkat. Mekanisme penulisan, siswa kesulitan dalam ejaan, tanda baca, dan pilihan kata. Kosakata, siswa kesulitan menggunaan kata ganti orang, kata ganti abstrak, kata benda umum, kata kerja, kata keterangan, kata sifat. Untuk isi, siswa dapat menulis teks, tapi kesulitan pada relevansi antara ide pokok, pendapat, dan rekomendasi. Â  Kata kunci: Identifikasi, kesulitan siswa, hortatori exposisi